Cultural difference and economic disadvantage in regional human rights courts : an integrated view - David, Valeska (Cambridge, United Kingdom : Intersentia, 2020)
"More and more people are turning to human rights courts to seek protection against prejudice, disadvantage or exclusion on account of their cultural and economic particularities. Human rights courts are thus increasingly faced with the difficult task of deciding these cases, which raise a number of complex and contested legal questions. To what extent can courts accommodate cultural diversity, protect all kinds of groups or interfere in socio-economic policy? This book argues that one of the problems encountered in dealing with such cases is the courts' tendency to assess them from a 'compartmentalised' or fragmentary perspective. To counterbalance this tendency, an innovative, integrated and person-centered approach to adjudicating claims of cultural difference and economic disadvantage is put forward. Drawing on the concepts of intersectionality, indivisibility and normative interdependence, the book presents specific notions and methods for approaching the appreciation of rights holders, harms and norms in a holistic manner. A wide selection of case law from both the European and the Inter-American courts of human rights supports the normative framework developed in this book. The sample mostly includes cases brought by Muslims, Roma, Travelers, indigenous peoples, Afro-descendants and people living in poverty"--Back cover.
Introduction -- A conceptual and normative exploration -- An integrated approach to cultural difference in the European Court of Human Rights -- An integrated approach to cultural difference in the Inter-American Court of Human Right -- An integrated approach to economic disadvantage in the European Court of Human Right -- An integrated approach to economic disadvantage in the Inter-American Court of Human Rights {u2013} Conclusion.
Includes bibliographical references (pages 383-402) and index.
Keywords: International human rights courts; Human rights; Minorities -- Legal status, laws, etc; Legal assistance to the poor; Human rights; International human rights courts; Legal assistance to the poor; Minorities -- Legal status, laws, etc